The Effect of Fiscal and Monetary Policy on Public Debt in Egypt - Mohamed, Malak (AUC Knowledge Fountain, 2024)
The thesis aims to examine the effect of monetary policies and fiscal policies on public debt in Egypt during the period from 2006 until 2021. Egypt is witnessing aggravated levels of debt, with limited fiscal and monetary space. Therefore, the objective of the paper is to analyze the effect of discount rates, inflation rates, subsidies, taxes and economic growth on debt-to-GDP in Egypt using a VAR model with an extended test of Impulse Response Function. The results suggest that a positive shock in government expenditures initially decreases public debt but leads to a fluctuating increase in the debt-to-GDP ratio in the long run. Tax increases initially reduce the debt to GDP ratio. A positive shock in inflation rates increases the debt to GDP ratio initially but shows a negative effect in the longer term. Additionally, a positive shock in discount rates leads to a higher debt to GDP ratio in the long run due to higher cost of debt service. The findings conclude that the interactions between fiscal and monetary policies are quite complex and interrelated, and require policy makers to consider their effect on the long and short run. The thesis also highlights the significant risk for Egypt to fall in a debt-inflation trap.